PENGARUH KEADILAN PAJAK, PENGETAHUAN PAJAK, SANKSI PAJAK DAN KONSULTAN PAJAK TERHADAP KEPATUHAN WAJIB PAJAK USAHA MIKRO KECIL MENENGAH PADA KANTOR PELAYANAN PAJAK PRATAMA DENPASAR BARAT - Desak Nyoman Widiasih; Ni Luh Putu Wiagustini (Universitas Triatma Mulya, 2020)
Taxpayer compliance is an important issue of concern for developing and developed countries. The issue of taxpayer compliance is closely related to tax revenue. Non-compliant taxpayers will cause a desire to avoid, evade, smuggle and neglect tax, which will cause tax revenues to be reduced. This research was conducted to determine tax fairness, tax knowledge, tax sanctions and the role of tax consultants on tax compliance for micro small and medium enterprises in KPP. Pratama West Denpasar. This research is a quantitative research. The population in this study is the taxpayers of micro small and medium enterprises registered at the Tax Office. Pratama West Denpasar. The sample was determined using the Sample Random Sampling method with 120 micro and small businesses. Data collection techniques are carried out by distributing questionnaires to taxpayers. The model used is multiple linear regression. The results of this study are tax justice, tax knowledge, tax sanctions and the role of tax consultants have a significant positive effect on the level of tax compliance of micro small and medium enterprises.Keywords: tax justice, tax knowledge, tax sanctions, role of tax consultants, taxpayer compliance.